The European Integration of Higher Education and the Role of Private Higher Education - Kwiek, Marek (My University, 2007)
The Bologna process—a major European integrating initiative in higher education started by the Bologna Declaration in 1999 and to be completed by 2010—seems to disregard one of the most significant recent developments in several major post-communist transition countries in Central and Eastern Europe: the rise and rapid growth of the private sectors in higher education and, more generally, the emergence of powerful market forces in higher education. Consequently, the ideas behind the Bologna process, the analytical tools, and policy recommendations it provides may have unanticipated effects on higher education systems in certain Central and Eastern European countries. The growth of both the private sector in European (and especially Central and East European) higher education systems and the emergence of powerful market forces in the educational and research landscape in Europe warrant further consideration by the Bologna process if it is not to turn into a merely "theoretical," myopic exercise. The downplaying of the role of market forces in higher education and research and development in the Bologna documents and the omission of the private sector (with its evident successes in some places and failures in other places)from the overall conceptual scheme of the Bologna process give potentially misguided signals to educational authorities in transition economies. Consequently, the Bologna process might thwart the development of the private sector in countries where chances for the expansion of the educational system otherwise than through privatization have been limited.
Keywords: Bologna Process; European integration; higher education; Europe; privatization; private sector; private higher education; market; marketization; public-private; competition; fees; Poland; Daniel C. Levy; post-communist higher education; Bologna Declaration; Eastern Europe